Faustovirus-Like Asfarvirus in Hematophagous Biting Midges and Their Vertebrate Hosts - Temmam, Sarah; Monteil-Bouchard, Sonia; Sambou, Masse; Aubadie-Ladrix, Maxence; Azza, Saïd; Decloquement, Philippe; Khalil, Jacques Y. Bou; Baudoin, Jean-Pierre; Jardot, Priscilla; Robert, Catherine; La Scola, Bernard; Mediannikov, Oleg Y.; et al. (Frontiers in Microbiology, 2015)
Faustovirus, a new Asfarviridae-related giant virus, was recently isolated in Vermamoeba vermiformis, a protist found in sewage water in various geographical locations and occasionally reported in human eye infection cases. As part of a global metagenomic analysis of viral communities existing in biting midges, we report here for the first time the identification and isolation of a Faustovirus-like virus in hematophagous arthropods and its detection in their animal hosts. The DNA virome analysis of three pools of Culicoides sp., engorged female C. imicola and non-engorged male/female C. imicola biting midges collected in Senegal, revealed the presence of amoeba-infecting giant viruses and, among them, a majority of sequences related to Faustovirus. Phylogenetic analyses conducted on several structural genes of Faustovirus confirmed the clustering of the arthropod-borne Faustovirus with sewage-borne Faustoviruses, with a distinct geographical clustering of Senegalese Faustovirus strains. Transmission electron microscopy identified viral particles with morphologies and diameters which were compatible with Faustovirus. The presence of infectious arthropod-borne Faustovirus was finally confirmed by successful isolation on V. vermiformis amoeba. Global proteomic analysis of biting midges identified that arthropods’ blood meal originating from cattle, rodents and humans. Further screening of cattle sera and rodent tissue resulted in prevalence of Faustovirus being estimated at 38% in rodents and 14% in cattle, suggesting a possible origin of Faustovirus presence in arthropods via the ingestion of contaminated blood meal. Viral loads were the highest in rodents’ urine and kidney samples, suggesting a possible excretion of viral particles into the environment. Faustovirus DNA polymerase-related sequences were also detected in more than 9% and 11% of febrile patients and healthy Senegalese human sera, respectively. Our study thus highlights the need to investigate the role of arthropods, wildlife and domestic animals in the lifecycle of amoeba-infecting giant viruses and, in particular, the environmental cycle of Faustovirus.